English extracurriculars and anxiety levels: a quantitative examination among first-year university students - Hien Nguyen T. Dieu; Ngoc Nguyen T. Nhu; Quyen Kieu Minh (Cogent Education, 2024)
AbstractIn a supportive and immersive environment, engaging in English extracurricular activities is crucial for university students as it enhances their language skills, cultivates valuable communication and teamwork abilities, and significantly alleviates their anxiety levels. This quantitative study aimed to examine the causality between the independent variable (intervention in English extracurricular activities—EECAs) and the dependent variable (learners’ anxiety levels) using the Foreign Language Anxiety Scale developed by Horwitz et al. Data were collected from a sample of 306 first-year students at a university in Vietnam through self-report surveys administered both before and after participating in EECAs. The analysis of the collected data employed descriptive statistics and paired sample t-tests, revealing a causal relationship between participation in these activities and language learners’ anxiety levels. The results revealed that active involvement in extracurricular activities may reduce learners’ anxiety levels. These findings emphasize the significance of considering the potential impact of extracurricular activities on learners’ anxiety levels and call for further research and interventions to address and alleviate anxiety in language learners involved in such activities.